Strategi Komunikasi Radio Songgolangit FM dalam Menarik Minat Pendengar Studi Kasus Program Jumat Berkah - Feby Ayu Rusmayanti (Program Studi Komunikasi dan Penyiaran Islam, Fakultas Dakwah, Institut Agama Islam Sunan Giri Ponorogo, 2022)
Radio Songgolangit FM is one of the major radio stations in Ponorogo Regency with a large number of listeners. Feeling that all of this is not enough, Radio Songgolangit FM also holds a program that can maintain its existence and attract listeners, namely Friday blessing. Departing from this, it makes researchers interested and want to know how the implementation of the Friday blessing program is and what is the purpose of the Friday blessing program on Radio Songgolangit FM. For this reason, the writer is interested in conducting research on Songgolangit FM Radio in the form of a scientific paper with the title